METABOLIC AND AUTOIMMUNE RISK FACTORS FOR CORONARY ARTERY DISEASE (CAD) IN HEART TRANSPLANT RECIPIENTS - T. A. Khalilulin; O. V. Orlova; B. L. Mironkov; V. V. Chestuhin; E. N. Kazakov; A. J. Kormer; О. P. Shevchenko (Вестник трансплантологии и искусственных органов, 2010)
One of the most essential autoimmunity risk factors for development of CAD are increasing level of anticardiolipin antibodies and homocystein. This report presents retrospective analyses of 39 heart transplant recipients with maximal follow up over 16 years. Our results showed that hyperhomocystenemia and high levels of anticardiolipin antibodies play great value in development of CAD. Thus relative risks for development of CAD in presence both high levels of anticardiolipin antibodies and homocysteine are higher, than in traditional nonimmune risk factors.